PELAYANAN HOME CARE BERBASIS RUMAH SAKIT STUDI KASUS PELAYANAN HOME CARE BERBASIS RUMAH SAKIT SARDJITO YOGYAKARTA TERHADAP LANJUT USIA DENGAN STROKE - Titik Endarwati; I Dewa Putu Pramantara S.; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Home care service that empowers family caregivers enhance the ability, making independent in the care of patients at home, reduce or prevent dependence on formal services. In contrast, business-oriented without empower family caregivers are part of the hospital health care industrialization. Objective: to describe the characteristics of family caregiver’s independence caring for elderly in post-stroke at home and empower family caregivers in the services of hospital-based home care from the perspective of family caregivers. Methods: This study used a qualitative approach with exploratory case study design. The unit of analysis is the empowerment of family caregivers in the context before discharge from the hospital and after at home (home care context) based Sardjito’s Hospital. Subjects in this study were 4 family caregivers, the husband, wife, and children from 3 elderly poststroke patients Sardjito Hospital. The sampling method used is purposive sampling. Results: Characteristics of the independence of family caregivers that have: 1) knowledge of the fulfillment of the needs of the elderly ADL; 2) confidence in meeting the needs of the elderly ADL; and 3) the ability to meet the needs of elderly ADL, fix the problem, seek the information needed, utilizing the nurses home visits, and provides tools and materials medical. Educating family caregivers, involving family caregivers in planning and decision-making, and assured the role of family caregivers is a strategy to empower family caregivers. An empowerment strategy done continuously that started at the hospital and continued at home. Conclusions: Family caregiver empowerment strategy in hospital-based home care services increase the independence of family caregivers in caring for the elderly post-stroke.